Tipe pola asuh orang tua yang berhubungan dengan perilaku bullying pada pelajar SMP - Dhini Easter Yanti; Teguh Pribadi; Anhar Jaya Putra (Holistik Jurnal Kesehatan, 2020)
Indonesian parenting styles and bullying among junior high school students, Bandar Lampung-IndonesiaBackground: The data base of  Child Protection Committee in Indonesia  2011-2014 had been  increasing and is ranked at the top of 369 cases reported to Child Protection Committee such as in education enviroment, bullying behaviour among students at the schools  was very common. The reason of the student has a bullying behaviour  can be from various factors such as parenting styles of their parent.Purpose: To know the relationship between  parenting styles and bullying among junior high school students, in Bandar Lampung-IndonesiaMethod: A quantitative research type by using a cross sectional approach. The population were all students of grade VII and VIII at Gajah Mada junior high School in Bandar Lampung, Indonesia, with the sample 153 respondents. Data collection techniques were carried out by questionnaire. The statistical test used by the chi square test.Results: Most respondents claim uninvolved a school bullying, as much as 111 students (72.5%). Most of the respondents  claim have a democratic parenting styles by their parent as many as 78 respondent (51.0%). There is a relationship between parenting styles and bullying among junior high school students, Bandar Lampung-Indonesia in 2019 with p-value <α (0,000 <0.05)Conclusion: There is a relationship between parenting styles and bullying among junior high school students,Bandar Lampung-Indonesia. Suggestions for educational institutions, it is hoped that the results of this study can be a means and reference for educators / schools in overcoming the problem of school bullying among junior high school students by informing to the parents to be applying appropriate a parenting style to their children.Keywords: Parenting styles; Bullying; Junior high school; StudentsPendahuluan: Kasus bullying menurut KPAI pada tahun 2011-2014 juga semakin meningkat dan menduduki peringkat teratas sebanyak 369 pengaduan kepada KPAI, dalam bidang pendidikan seperi kekerasan di sekolah, diskriminasi terdapat sekitar 1480 kasus.  Penyebab seseorang menjadi pelaku “bullying” bisa dari berbagai faktor seperti orang tua yang terlalu memanjakan anaknya.Tujuan: Diketahui hubungan pola asuh orangtua dengan perilaku bullying pada siswa SMP Gajah Mada Kota Bandar Lampung Tahun 2019.Metode: Penelitian kuantitatif, menggunakan pendekatan cross sectional. Populasinya seluruh siswa  kelas VII dan VIII di SMP Gajah Mada Bandar Lampung  pada tahun 2019 yaitu sebanyak 246 orang. Sampel 153 responden. Tehnik pengumpulan data dilakukan dengan kuesioner. Uji statistik yang digunakan adalah uji chi square.Hasil: Sebagian besar responden mengaku tidak melakukan perilaku bullying yaitu sebanyak 111 orang (72,5%). Sebagian besar responden mengaku memiliki pola asuh orang tua yang demokratis sebanyak 78 orang (51,0%). Terdapat hubungan pola asuh orangtua dengan perilaku bullying pada siswa SMP Gajah Mada Kota Bandar Lampung Tahun 2019 dengan nilai p-value < α (0,000 < 0,05)Simpulan: Ada hubungan pola asuh orangtua dengan perilaku bullying. Saran kepada institusi pendidikan, diharapkan hasil penelitian ini dapat menjadi sarana dan referensi bagi pihak pendidik/ sekolah dalam mengatasi masalah bullying pada remaja dengan memberkan informasi pada oraang tua supaya dapat menerakan pola asuh yang tepat bagi anaknya.